What to Do When Septic Systems Are Impacted by Flooding from Storms or Groundwater Rise - Mary G. Lusk (EDIS)
The purpose of this publication is to explain how septic systems may be affected by floods from hurricanes and other storms and/or by climate change (sea-level rise) that raises the level of the groundwater under septic system soils. Written by Mary G. Lusk, and published by the UF/IFAS Department of Agricultural and Biological Engineering, November 2023.